The origins of [C ii] emission in local star-forming galaxies - Croxall, KV; Smith, JD; Pellegrini, E; Groves, B; Bolatto, A; Herrera-Camus, R; Sandstrom, KM; Draine, B; Wolfire, MG; Armus, L; Boquien, M; Brandl, B; et al. (Institute of Physics, 2017)
The [C II] 158 μm fine-structure line is the brightest emission line observed in local star-forming galaxies. As a major coolant of the gas-phase interstellar medium, [C II] balances the heating, including that due to far-ultraviolet photons, which heat the gas via the photoelectric effect. However, the origin of [C II] emission remains unclear because C+ can be found in multiple phases of the interstellar medium. Here we measure the fractions of [C II] emission originating in the ionized and neutral gas phases of a sample of nearby galaxies. We use the [N II] 205 μm fine-structure line to trace the ionized medium, thereby eliminating the strong density dependence that exists in the ratio of [C II]/[N II] 122 μm. Using the FIR [C II] and [N II] emission detected by the KINGFISH (Key Insights on Nearby Galaxies: a Far- Infrared Survey with Herschel) and Beyond the Peak Herschel programs, we show that 60%–80% of [C II] emission originates from neutral gas. We find that the fraction of [C II] originating in the neutral medium has a weak dependence on dust temperature and the surface density of star formation, and has a stronger dependence on the gas-phase metallicity. In metal-rich environments, the relatively cooler ionized gas makes substantially larger contributions to total [C II] emission than at low abundance, contrary to prior expectations. Approximate calibrations of this metallicity trend are provided.